Radicals by Design - Anna K. Croft; Karl B. Lindsay; Philippe Renaud; Troels Skrydstrup (CHIMIA, 2008)
Radical reactions offer many advantages over conventional chemical reactions, lending themselves to numerous bond forming processes and rearrangements that are, clean, rapid, and tolerant of a wide range of functional groups. This review provides a brief overview of the design concepts behind new reactions illustrating, in particular, their relevance for the efficient synthesis of biomolecules. Two general reactions are highlighted: single electron transfer (SET) using SmI2 and hydrogen transfer using reagents such as those based on tin, thiols and phosphorous reagents. Intermolecular influences that may direct radical reactions, such as partial protonation and radical complexation, are also discussed.